Motivação e invalidades do ato administrativo - Castro, Taiane Lobato de (2008)
The objective of this study is to address, within the Brazilian legal system, the duty of motivation of administrative acts and the consequence of its non compliance. Such option is justified as the administrative acting must always be guided by the reasons for its acts. We do not see any basis to be otherwise. The single paragraph of article 1st of the Federal Constitution is categorical in saying that all power comes from the people, who exercises it through elected representatives or directly. Thus, based on constitutional device, there must be no darkness or lack of motivation of administrative acts. Documentary research and literature of national and foreign authors, as well as our Court decisions, led us to the result that the motivation must be considered a sublime principle to be pursued by the Administration, as it represents true guarantee to the people, and, if not observed, there could be either a voiding or a validating act, provided that it has been verified in a case and the real consequences in the legal sphere of the people